Photometric Techniques for Exploring Multiple Populations in Clusters. (5th March 2015) - Anderson, Jay
Abstract: The advent of the Hubble Space Telescope (HST) and the development of new photometric algorithms that take advantage of its stable observing platform above the atmosphere have allowed us to study the populations in globular clusters with very high precision.